Tax Stimulation of Attracting a Foreign Investments in Economy of Ukraine in the Conditions of Financial Instability (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article the basic results of reformation of the tax system of Ukraine are reflected as a result of tax reform of 2016 year. It is well-proven that estimating efficiency of tax mechanism of bringing a foreign investment is possible probing the tax loading in a country. Determination of term «tax loading» and analysed of indexes of the tax loading is conducted on the subjects of the economic system. Found out dependence between the level of the general tax loading and volume of foreign investments in Ukraine during 2012–2015 years. The place of our country in the world financial ratings of attractiveness of economy and Paying of taxes-2016 are investigational. The necessity of account of foreign experience is well-proven at reformation of the tax system in part of decline of the tax loading. The directions of improvement of tax stimulation of foreign investments in economy of Ukraine in the conditions of financial instability are grounded.
Keywords: investments, foreign investments, taxes, tax reform, tax loading, tax stimulation, investment climate